2SPD-002 Improvement in an antimicrobial stewardship programme after implementing a screening alert system. (24th March 2020) - Tevar, E; Castillo Méndez, MJ; Ferrer Machín, A; Padilla Salazar, ML; Abella Vázquez, L; Ode Febles, J; Álvarez Tosco, K; Hayek Peraza, M; Gómez, MÁ Ocaña; Merino Alonso, J
Abstract : Background and importance: The implementation of an antimicrobial stewardship programme (AMSP) is very important but it has to be accompanied by personnel resources. It is therefore necessary to effectively use the time spent in the AMSP reviewing only those treatments that can be improved. Aim and objectives: To implement a screening alert system (SAS) that shows only those antibiotic treatments that could be improved by meeting predefined conditions and to evaluate the SAS. Material and methods: This was a quasi-experimental study. Using the information available in the electronic health record (EHR) and in the pharmacy and microbiology applications, we developed a computer tool that analysed hundreds of situations under pre-established conditions. For one month, before each AMSP team meeting, we recorded the total number of patients and prescribed antibiotics in the hospital compared with the number of treatments and patients that our system proposed to review. The main variable of our study was number of patients to check before and after the tool. Secondary variables included number of antibiotics to review. For the statistical analysis, the paired t test was used to determine if there were differences in the mean number of patients reviewed before and after using the SAS. The analyses were performed using SPSS/PC statistical programme (V.24.0 for Windows, SPSS Inc, Chicago, Illinois, USA). Results: Seven services were included in the study: vascular surgery, cardiology, general surgery, geriatrics, internal medicine, neurology and traumatology. The number of antibiotics to review without the SAS in each AMSP team meeting was 21 (7–22) compared with 7 (3–9) when we used the SAS. Mean differences were found for patients to theoretically check before using the SAS (14±7 patients) compared with those who were actually checked after using the tool (5±3 patients) (mean difference 9 (95% CI 5 to 12 patients); p=0.000124). Conclusion and relevance: This software allows the collection of information contained in different systems and displays only the relevant one in an organised view for the user. Limited personnel resources make the development of screening systems essential to optimise time and to prioritise which treatments need to be reviewed. References and/or acknowledgements: 1. Rodríguez-Baños J, et al. Programs for optimizing the use of antibiotics (PROA) in Spanish hospitals: GEIH-SEIMC, SEFH and SEMPSPH consensus document. Farm Hosp 2012;36(1). No conflict of interest.